THE DIRECT EFFECTS OF THE CORONAVIRUS 19 ON CHILDREN IN IRAQ - Ali Rashed Abd Alsryawe; Kahtan Adnan Abdullah; Mahdi Misraa Breessm (Scholar Express Journals, 2022)
The study aims to know the direct effect of CO-19 on children and this study was conducted in different Hospitals in Iraq, where 100 children were collected for the purpose of describing the features and demographic characteristics of children patient with CO-19. Coronavirus in children is still considered a mysterious disease. It is believed to be asymptomatic and not at all dangerous to children and adolescents. But there is also evidence of the severity of the disease, its risks, and long-term negative effects on the children's body. In childhood, infection with coronavirus is less common than in adults, but cases of the disease have been recorded in Iraq. Moreover, the infection rate is increasing, as evidenced by the statistics
Keywords: CO-19; Children; MERS; Symptoms